Teaching English Using Multiple Intelligences Approach in Lazuardi Kamila GIS Elementary School in 2014-2015 Academic Year - Ayuningtyas, Ristianah, Mauly Halwat Hikmat, Ph. D, Dr. Anam Sutopo, M.Hum (2016)
This thesis is written1)to know whether the syllabus in the implementation of Multiple Intelligence Approach in LazuardiKamilaGIS Surakarta; 2) to know whether the learning objectives in the implementation of Multiple Intelligence Approach in LazuardiKamilaGIS Surakarta; 3) to observe whether the procedures in the implementation of Multiple Intelligence Approach in LazuardiKamilaGIS Surakarta; 4) how the assessment in the implementation of Multiple Intelligence Approach in LazuardiKamilaGIS Surakarta; 5) how the teachers' roles in applying the Multiple Intelligences Theory in the classroom setting; and 6) how students response to the Multiple Intelligence Approach. 7) to know whether the benefit and challange of Multiple Intelligence Approach. The writer uses qualitative research at LazuardiKamila GIS Surakarta. The research was conducted from February until April 2015 at the fourth grade.The source of data in this study consists of Primary data and Secondary data. Primary data is directed from investigation of the teacher in teaching English. Secondary data are events, document and human. The document can be form as syllabus. Then, human can be from the interview of teachers and students. Before the researcher finds the detail problems, she bundles the detail ones in the major problem. It is to ascertain teaching English using Multiple Intelligence Approach at Lazuardi Kamila GIS . The resultof this research shows that teaching English using Multiple Intelligences Approach is implemented in LazuardiKamila GIS Solo are drawn as follows: 1) the syllabus which is taken by the teachers' in LazuardiKamila GIS follows the government's syllabus but the teacher must adjust according to the students ability. 2) The learning objective is included in syllabus but in LazuardiKamila GIS, it must be appropriate to the students. 3) the procedure of teaching learning process done by the teacher to the students. They are: a) alpha zone b) scene setting c) main activities d) closing (giving feedback). 4) the assessmentin MI classroomconcerns not only on the students achievement, but also while process. 5) In conducting English lesson teacher played certain important roles. They are: a) facilitator, b) input provider, c) monitor of students' learning. 6) the implementation of MI in English classroom makes the students interested in learning and eases them to retrieve learning material so that they can achieve the learning objectives. 7) besides, MI implementation in English language teaching has more both benefits than challenges. The benefits covered creating fun learning in classroom, eliciting students' participation, and helping the students to obtain learning material. Then, it raised difficulties for the teacher in managing classroom dynamics when the students were not satisfied by the facilities provided by the teacher and in treating the students with special needs. Key words: teaching English, Mulitiple Intelligence, Elementary School, Young Learners.